4Korners Activities - 4 Korners Family Resource Center (2023)
Number of pages: 20

4Korners Activities - 4 Korners Family Resource Center (2023)
Number of pages: 26

4Korners Activities - 4 Korners Family Resource Center (2023)
Number of pages: 30

4Korners Activities : Hello March! - 4 Korners Family Resource Center (2023)
Number of pages: 32

4Korners Activities : Hello February! - 4 Korners Family Resource Center (2023)
Number of pages: 26

4Korners Activities - 4 Korners Family Resource Center (2023)
Number of pages: 28

CHSSN Senior Wellness Centre Initiative Activity Report Year 2 (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Senior Wellness Centre Initiative Activity Report (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 14

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 22

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 24

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 22

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 10

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 10

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 14

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 13

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 12

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 18

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 22

4Korners Activities - 4 Korners Family Resource Center (2022)
Number of pages: 15

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 13

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 19

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 15

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 16

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 14

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 20

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 18

4Korners Activities - 4 Korners Family Resource Center (2021)
Number of pages: 27

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 23

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 22

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 14

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 11

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

4Korners April 2020 - 4 Korners Family Resource Center (2020)
Number of pages: 10

August 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 6

June 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 7

May 2019 4K Newsletter - 4 Korners Family Resource Center (2019)
Number of pages: 5

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)
Number of pages: 6

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 9

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 10

Améliorer la santé et le bien-être des Madelinots anglophones : Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
La stratégie décrite dans le présent document est conçue comme une proposition à discuter avec les membres de la collectivité et les autres intervenants, et qui peut être adaptée et précisée au besoin. Elle est fondée sur une documentation pertinente en la matière et sur une évaluation des besoins réaliseee avec la contribution des acteurs locaux. Cette stratégie fait partie d'un processus de développement communautaire en continu, lequel a permis de réaliser un portrait de la communauté, des consultations publiques et un certain nombre d'actions qui s'inscrivent dans le cadre de la vision pour "Une communauté dynamique et en santé, sans drogues, sans alcool, ni violence, assurant un environnement favorable pour tous les membres de la communauté."
Keywords: Official Language Minority Community (OLMC)

Improving the Health and Well-Being of English-Speaking Magdalen Islanders : A Strategy for the Healthy Development of Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
The strategy outlined in this document is meant as a draft to be discussed with community members and other stakeholders, and to be adapted and refined as seen fit. It is based on current relevant literature, and a needs assessment carried out with input from local stakeholders. This strategy is part of an on-going community development process, which has included a community profile, community consultations, and a number of actions being carried out in the pursuit of the vision for “A dynamic, healthy community, free of drugs, alcohol and violence, with a supportive environment for all community members.”
Keywords: Official Language Minority Community (OLMC)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 7

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)
Number of pages: 8

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)
Number of pages: 24

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Parallel title: School & Community Resources - Working Together is the Key!
Keywords: Official Language Minority Community (OLMC)

A Needs Assessment : Better Understanding Substance Use Among Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
This needs assessment was requested by the Council for Anglophone Magdalen Islanders (CAMI) in preparation for the development of a strategy to address substance use among young people in Gross-ile, a concern identified by community members.
Parallel title: Improving the Health and Well-Being of English-Speaking Magdalen Islanders
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : Pour mieux comprendre la toxicomanie chez les jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2014)
Le Council for Anglophone Magdalen Islanders - CAMI (conseil des anglophones des Îles-de-la-Madeleine) a demandé que soit effectuée la présente évaluation des besoins en prévision de l'élaboration d'une stratégie visant à contrer la toxicomanie chez les jeunes, une préoccupation soulevée par des membres de la collectivité.
Parallel title: Améliorer santé et le bien-être des Madelinots anglophones
Keywords: Official Language Minority Community (OLMC)

Fall Prevention : Information for Clients and Their Families - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Youth Social Programs - Fequet, Shelley (Coasters Association)
The purpose of this document is to demonstrate the importance of having sustainable social programs available for youth living on the Lower North Shore. It is designed to give us the best understanding of the positive impacts social programs can have on our youth.

Wellness Centre for Seniors - Vision Gaspé-Percé Now